Welche Zukunft darf's denn sein? Mutige Annahmen bei der neuen Ifmo-Prognose "Mobilität 2025". - Hunsicker, Frank; Sommer, Carsten (Deutscher Verkehrs-Verl., 2008)
Vorhersagen zur Mobilität in ferner Zukunft sind sehr öffentlichkeitswirksam. Die dazugehörigen Annahmen und Prämissen im Hintergrund werden jedoch zu selten kritisch hinterfragt. Dabei wären Wirtschaft wie Politik dringend auf zuverlässige und realistische Perspektivaussagen angewiesen.

Forecasts about future mobility are of special interest to the public. Very often, the focus tends to be on the forecast-related results while relevant assumptions are rarely subject to any critical scrutiny. According to a recent study presented by the Institute for Mobility Research, until 2025, mobility-related public transport costs are to increase four times more than in the case of individual travel by private car. The latter will thus growth while public transport will decline correspondingly. A more detailed review of the main assumptions shows that, based on the average .actual price of oil held at only US $ 50/barrel until 2025, motorists will have to face only a small additional financial burden in spite of the anticipated introduction of road user charges for cars and the adoption of elaborate technical measures aimed at reducing climate-relevant emission. Surprisingly, there will be an increase in the level of private car traffic, whereby the cost per kilometer appears more favourable than specific decreases in the level of traffic. With regard to road traffic, the ifmo forecast is based on rather optimistic premises. Any discussions of future mobility should give prime consideration to realistic and objective perspectives.
Which future scenario appeals most?
Keywords: Verkehr; Verkehrsprognose; Verkehrsmittelwahl; Mobilität; Kostenschätzung; Verkehrsnachfrage; Verkehrsmodell; Modellrechnung; Mobilitätskosten